Calorific values and chemical composition of fast growing timber species - Chai, Ee Wen; H'ng, Paik San; Abdu, Arifin; Abdullah, Luqman Chuah (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Different timber species generally have different chemical composition and calorific values. In solid biofuel production, logs will be debarked. The bark may affect the calorific value because of its variable chemical composition. In this study, 2 to 5 yr-old fast growing timber species (Acacia spp., Endospermum spp., Macaranga spp., and Albizia falcataria) were harvested to determine the variation between chemical composition and calorific values. The correlation between the chemical composition and calorific value was determined using linear regression. The results showed that except for Macaranga spp., all other study species had high whole stem calorific value. Except for the positive correlation between calorific value and lignin content, correlations between the other variables were largely negative. In conclusion, calorific value is highly dependent on the chemical composition of the wood.